The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/cjce.5450780520
|View full text |Cite
|
Sign up to set email alerts
|

Gas flow regime changes in a bubble column filled with a fibre suspension

Abstract: Gas flow characteristics in opaque fibre suspensions have been captured on film using a stop‐motion X‐ray imaging technique called flash X‐ray radiography (FXR). Gas flows in a bubble column filled with various cellulose fibre suspensions from 0% (an air–water system) to 5% by mass have been observed. The gas flow regime changes from vortical to churn‐turbulent as the fibre concentration increases for a fixed superficial gas velocity. Two new gas flow regimes, identified as surge churn‐turbulent and discrete c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 17 publications
7
23
0
Order By: Relevance
“…When 0.6% ::; C ::; 1.5%, only the vortical-spiral flow and turbulent flow regimes appear, and the superficial gas velocity at which transition occurs is 13-14 cm/s, with the lower U. This is consistent with the observations of Reese et al [9] and Heindel [12] in semi-batch bubble columns. When Ug~5 cm/s, the slopes of the V g / e versus U g curves are not significantly different from those at C ::; 0.4%.…”
Section: Gas Flow Regime Transitionsupporting
confidence: 82%
See 1 more Smart Citation
“…When 0.6% ::; C ::; 1.5%, only the vortical-spiral flow and turbulent flow regimes appear, and the superficial gas velocity at which transition occurs is 13-14 cm/s, with the lower U. This is consistent with the observations of Reese et al [9] and Heindel [12] in semi-batch bubble columns. When Ug~5 cm/s, the slopes of the V g / e versus U g curves are not significantly different from those at C ::; 0.4%.…”
Section: Gas Flow Regime Transitionsupporting
confidence: 82%
“…Reese et al [9] found that in a 10.2 diameter cylindrical semi-batch bubble column filled with a fiber suspension, dispersed bubble, vortical-spiral, and turbulent flow could be identified when the fiber mass fraction was low (C S; 0.5%), while only dispersed bubble and turbulent flow were recordeã t high fiber mass fractions (C > 0.5%). In a I m t~1l2-D semibatch bubble column with a rectangular cross-secnon of 20 em x 2 em, Heindel [12] observed vortical, churn-turbulent, surge churn-turbulent and discrete channel flow as the fiber mass fraction increased from 0% to 5% with a fixed superficial gas velocity of 0.83 cm/s. In a 1.80 m tall 5.1 em diameter cocurrent bubble column, Xie et al [7] identified five distinct flow regimes in an air-water-cellulose fiber suspension, including dispersed bubbly, layered bubbly, (incipient plug and) plug, churn-turbulent, and slug flows.…”
Section: Introductionmentioning
confidence: 99%
“…When C > 0.6%, the slurry phase recirculation is suppressed, this was also reported by Lindsay et al (1995) and Heindel (2000Heindel ( ,2002, and is attributed to a decreased level of turbulence resulting from an increased slurry viscosity. This change in slurry flow characteristics results in fiber settling when Ug < 0.9 cm/s, causing a locally higher fiber mass fraction in the lower column region than in the upper column region.…”
Section: Effect Of Fiber Mass Fractionsupporting
confidence: 67%
“…However, fiber addition hindered small bubble coalescence in the cocurrent flow. In a semi-batch bubble column, Heindel (2000) observed that the number of small bubbles decreased and large bubbles increased with increasing fiber mass fraction. Bubbles rose upward in a serpentine flow pattern at low fiber mass fractions and this changed to a near vertical path at high fiber mass fractions.…”
Section: Bubble Behavior In Fiber Suspensionsmentioning
confidence: 98%
“…The presence of fibers can make the effective rheological properties of a fiber suspension significantly different from those of the suspending fluid [64][65][66]. Fiber floes or networks can significantly affect bubble motion, coalescence, and breakup, and thus, gas holdup in the bubble column [2,5,11,12,20,[67][68][69]. Pelton and Piette [69] reported that the main reason bubbles are held up in a fiber suspension is mechanical confinement, not bubble adhesion to fibers.…”
Section: Fiber Physical Propertiesmentioning
confidence: 99%